Evaluation of morning and evening milk of Holstein Friesian crossbred cows collected from Bangladesh Agricultural University Dairy Farm (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was undertaken to evaluate the organoleptic, specific gravity, chemical and microbiological qualities of morning and evening milk which collected from Bangladesh Agricultural University Dairy Farm, Mymensingh. In this purposes, six Holstein Friesian crossbred cows were selected for this study. Milk samples were collected every morning and evening immediately after milking and then subjected to test all mentioning parameters. Morning milk showed less yellowish than evening milk whereas flavor, body and texture were found normal in both intervals of milk. Specific gravity was found higher (1.030 ±0.000) in morning milk than evening and significantly (p